Exploring the virtual world of learning across generations: Information and communications technology for the educational support of immigrant youth - Rojek, Marcin; Leek, Joanna; Svoboda, Petr (Wydawnictwo Uniwersytetu Łódzkiego, 2020)
The book addresses the issue of intergenerational learning in a virtual world created by information and communication technology (ICT) and the role of ICT in an educational environment. In order to discuss how ICT can be used as a means to prevent early school leaving among immigrant youth, this book explores the literature on how learning can be understood in the intergenerational context, the challenges in preventing early school leaving, the prospects for ICT in education and presents the findings of an empirical study on intergenerational learning with the use of ICT. Authors findings highlight that ICT-supported intergenerational learning is a significant sociocultural platform for knowledge exchange, at the same time reducing intergenerational and cultural distance. It creates a sense of belonging and ensures mutual support, and encourages better understanding and harmonious coexistence between young immigrants and older citizens.